Stress triaxiality influence on damaging micromechanisms in a pearlitic ductile cast iron (Fracture and Structural Integrity, 2014)
In the last decades, damaging micromechanisms in ductile cast irons (DCIs) have been widely investigated, considering both the matrix microstructure and the loading conditions influence. Considering the graphite nodules, they were initially considered as voids embedded and growing in a ductile metal matrix (especially considering ferritic ductile cast irons). Recent experimental results allowed to identify a more complex role played by the graphite nodules, depending on the matrix microstructure.In this work, damaging micromechanisms in a pearlitic DCI were investigated by means of tensile tests performed on notched specimen, mainly focusing the role played by graphite elements and considering thestress triaxiality influence.
Keywords: Damaging micromechanisms